2021
DOI: 10.1186/s12951-021-00977-3
|View full text |Cite
|
Sign up to set email alerts
|

A novel multi-functionalized multicellular nanodelivery system for non-small cell lung cancer photochemotherapy

Abstract: Background A red blood cell membrane (RBCm)-derived drug delivery system allows prolonged circulation of an antitumor treatment and overcomes the issue of accelerated blood clearance induced by PEGylation. However, RBCm-derived drug delivery systems are limited by low drug-loading capacities and the lack of tumor-targeting ability. Thus, new designs of RBCm-based delivery systems are needed. Results Herein, we designed hyaluronic acid (HA)–hybridiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 78 publications
0
23
0
Order By: Relevance
“…Studies have also shown near infrared (NIR) light-initiated and pH-triggered drug release. Drug release studies by many researchers have established that RBC-based drug delivery systems are advantageous in terms of prolonged circulation time and sustained release ( Zhang et al, 2021 ).…”
Section: Characterization Of Red Blood Cell-derived Particlesmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have also shown near infrared (NIR) light-initiated and pH-triggered drug release. Drug release studies by many researchers have established that RBC-based drug delivery systems are advantageous in terms of prolonged circulation time and sustained release ( Zhang et al, 2021 ).…”
Section: Characterization Of Red Blood Cell-derived Particlesmentioning
confidence: 99%
“…Combinatorial therapy involving two therapies at the same time is been carried out to achieve better efficacies. Doxorubicin (DOX)-loaded into hollow prussian blue nanoparticle ( Chen et al, 2017 ), paclitaxel and IR-780 co-loaded in lipid multi-chambered nanoparticles ( Zhang et al, 2021 ) and DOX-loaded hollow copper sulfide (CuS) nanoparticles ( Wang et al, 2018 ) were administered for light activated combinatorial therapies of cancer. All these nanoparticles were RBC-cloaked helping them to escape from the reticuloendothelial system (RES) and immune evasion, achieving longer circulation.…”
Section: Applications Of Red Blood Cell Membrane-derived Systemsmentioning
confidence: 99%
“…For example, to enhance the specifical targeting ability to non-small cell lung cancer cells (A549) with high expression of CD44, hyaluronic acid (HA), the receptor of CD44, was applied to insert into RBCm. ( Zhang et al, 2021c ).…”
Section: Engineering Of Biomimetic Membrane For Improved Drug Deliverymentioning
confidence: 99%
“… Strategy Cell membrane Modifier Nanoparticle Effects Ref. Lipid insertion RBC HA-DOPE PTX, IR780 Actively targeting A549 cells ( Zhang et al, 2021c ) RBC RGD-PEG-DSPE CS-6, DOX Actively targeting TNBC cells ( Fan et al, 2020 ) RBC RGD-PEG-DSPE Black phosphorus Improving tumor targeting by specifically recognizing ανβ 3 ( Zhong et al, 2021 ) RBC cRGD-PEG-DSPE DACHPt, ICG Actively targeting cancer tissues, enhancing tumor-specific cellular uptake ( Liu et al, 2018b ) RAW 264.7 T7-PEG-DSPE Saikosaponin D/PLGA Targeting ligands transfer ferritin receptors overexpressed in tumor cells ( Sun et al, 2020 ) RBC DIR PTX-PN Providing powerful heat energy and promoting the release of core drugs under laser irradiation ( Su et al, 2016 ) A549 Liposome with MMP-9-sensitive peptide PC@CO-LC Promoting tumor cell penetration, pH triggered membrane rupture and drug release ( Zhang et al, 2021b ) Membrane hybridization RBC NCI-H1299 lung cancer cell PLGA/DOTAP/SAHA Prolonging blood circulation time and homotype targeting of metastatic cells ( Peng et al, 2021 ) 4T1 RAW 264.7 DOX/PLGA Accumulating at inflammation sites and targeting specific metastasis ( Gong et al, 2020 ) Metabolic engineering 4T1 Azide-cho, anti-CD205 MNCs Preferentially recognized by CD8+ dendritic cells ( …”
Section: Engineering Of Biomimetic Membrane For Improved Drug Deliverymentioning
confidence: 99%
“…They can also be used in targeted delivery applications to uptake the drugs to specific sites. Furthermore, the ease of large-scale manufacturing and storage, improved stability, and healthy yet low-cost components have made niosomes an appealing alternative to conventional micro-and nano-encapsulation methods [14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%